Ayahuasca A Proving - Shukla, Chetna N. (Homœopathic Links, 2013)
Ayahuasca needs little introduction. The proving took me to Brazil and I took the journey with shamans and I had a beautiful rendezvous with myself. Thereafter I have used it also as a homeopathic remedy in individuals who know their nature but could not transform (stuck) and especially in drug addicts (cocaine, alcohol, allopathic drugs).
Keywords: Ayahuasca; Banisteriopsis caapi; Psychotria viridis; Psychedelic; Proving; Sofeggio frequencies; Icaros; DMT